Hot Property The Housing Market in Major Cities - Nijskens, Rob; Lohuis, Melanie; Hilbers, Paul; Heeringa, Willem (Springer International Publishing : Imprint: Springer, 2019)
This open access book discusses booming housing markets in cities around the globe, and the resulting challenges for policymakers and central banks. Cities are booming everywhere, leading to a growing demand for urban housing. In many cities this demand is out-pacing supply, which causes house prices to soar and increases the pressure on rental markets. These developments are posing major challenges for policymakers, central banks and other authorities responsible for ensuring financial stability, and economic well-being in general. This volume collects views from high-level policymakers and researchers, providing essential insights into these challenges, their impact on society, the economy and financial stability, and possible policy responses. The respective chapters address issues such as the popularity of cities, the question of a credit-fueled housing bubble, the role of housing supply frictions and potential policy solutions. Given its scope, the book offers a revealing read and valuable guide for everyone involved in practical policymaking for housing markets, mortgage credit and financial stability.